How effective is AAL? Results from an RCT among older persons in Austria. (13th November 2019) - Schmidt, L; Majcen, K; Löffler, K; Schuster, E; Augustin, T; Murg, S; König, C; Steiner, J
Abstract: Background: Many older people wish to remain in their own environment for as long as possible; an aim shared by the wider community. Here the results of the RegionAAL study (Steiermark, Austria) are reported. Methods: An RCT was implemented to evaluate a programme of interventions (e.g. medication, drink and physical activity reminders, automatic light systems, watches to detect falls, video telephone with carers). Data was collected via quantitative questionnaires at baseline, 6 months and 1 year regarding quality of life and carers' burden. Results: 111 persons and 104 carers took part in the intervention group; 110 participants and 100 carers in the control group. Participant characteristics were similar at baseline. Average age was 76 years. Around 1/3 were formal carers. A tendency for more persons in the control group to require assistance after one year could be observed. The subscales autonomy and participation of the WHOQOL-OLD showed some significant declines in the control group (no deterioration in the intervention group). No differences between study arms regarding general health, chronic conditions or hospital admissions were observed. Expected reduction in worry among carers could not be observed, although there was a tendency for some aspects of burden to be reduced. The interventions did not lead to a reduction in carers' workload; neither did the carers see any direct improvement of their situation. Conclusions: Some technologies such as cognitive games on the tablet, portable door bell and automatic light sensor were positively assessed. The participants in the intervention group scored better on autonomy and participation subscales than the control group; the intervention group also fared somewhat better regarding independence. The technologies had little influence on general health states or quality of life of participants or carers. Further good quality studies are needed before AAL technologies are considered as a public health initiative. Key messages: AAL may reduce aspects of worry among carers and prevent age-related decline in autonomy, participation and independence among older persons but not have an effect on general health status or burden. AAL has only a very limited impact upon general health status or quality of life of older persons and the general burden experienced by carers.